Analyze of Sensory (Color, Teksture, Taste) Wet Noodles Using Extract Peperromia Pellucida - Zahara, Ayu; Elida, Elida; Kasmita, Kasmita; Ul, Naseh (Universitas Negeri Padang, 2024)
This research aims to test and analyze the effect of using ketumpang water extract on the quality of wet noodles. This research is an experiment using 3 treatments, 2 of which are the same and one is different because it uses the triangle test or differentiation test. The data analysis technique used is using binominal data which includes the influence on color, namely at the 5% level, for texture also at the 5% level, and for taste also at the 5% level, which means that each is significantly different. And next (Analysis of Variance (ANOVA) to analyze the sensory test data, the average value for color X1 (2,57), X2 (16,33), X3 (1,00) was obtained. For the average value for texture X1 ( 3,67), X2 (14,00), X3 (2,33). For the average value of flavor X1 (3,67), X2 (14,00), X3 (2,33) The sensory test obtained a significant value or probability (sig) for the quality of color, texture and taste, namely 0.01<0.05, then continued with the Duncan test It was concluded that the test results for using ketumpang water extract on wet noodles were treatment (X2) with sensory code 523.